Eggs of twelve Siberian and Far Eastern Isoperlinae (Plecoptera: Perlodidae) - Teslenko, Valentina A. (Zootaxa, 2025)
Eggs of 12 Isoperlinae species from Siberia and the Russian Far East are examined, illustrated, and described using scanning electron microscopy images for the first time. Keys for their identification are proposed and included. East-Palaearctic Isoperla eximia Zapekina-Dulkeit, 1975 is recorded for Japan for the first time.